Water and sediment quality in the lower reaches of the sampadi river - Maczie, Palrick (Universiti Malaysia Sarawak (UNIMAS), 2012)
The study was conducted at the lower reaches of Sampadi River to determine the water quality and sediment status. Results showed that TSS were the highest at the station that received the discharge from upstream activities (83.87-99.60 mg/L) and shrimp aquaculture farm (266.40-282.13 mg/L). During LT, the stations near to the residential areas were the highest in ammonia nitrogen (0.209-0.227 mg/L) and TKN (0.289-0.346 mg/L) while at the station at the tributary of shrimp culture site showed the highest Zn (0.1096-0.1373 mg/L) and Pb (0.0148-0.0229 mg/L). During HT, the concentration of Ni (0.2727-3.032 mg/L), Cr (0.0131-0.0207 mg/L), TKN (0.198-0.299 mg/L) and NO2-N (0.019-0.037 mg/L) were all higher at the stations that received the discharge of aquaculture shrimp farm and residential area. Oil and grease HT was higher at station 5 which is nearer to the palm oil plantation with concentration of 28.0 mg/L. For sediment, the PSA showed that the sediments were sand to silty-loam categories. The station with high silt fraction also had the highest TOC. Silt content, TOC and TKN ranged from 12.23-74.19%, 2.59-5.42% and 896-1680 mg/kg. All the heavy metals in sediments had the highest at station 5 (silty-loam) and the lowest at stations 1 and 2 (both sandy).